Phylogenetic analysis of the scorpion genus Brachistosternus (Arachnida, Scorpiones, Bothriuridae) - Ojanguren Affilastro, Andres Alejandro (2009)
A phylogenetic analysis of the scorpion genus Brachistosternus Pocock (Bothriuridae) is presented. The analysis is based on a data set including 38 of the 41 described species of Brachistosternus plus eight outgroup representatives of seven additional bothriurid genera and one buthid, scored for 116 morphological characters. The cladistic analysis of this matrix under implied weighting results in four most parsimonious trees. The monophyly of genus Brachistosternus is well supported; its subgeneric subdivision is redefined: the subgenera Brachistosternus Pocock and Ministernus Francke are considered valid, whereas Leptosternus Maury is synonymized with Brachistosternus. Illustrations of diagnostic structures are provided. The hemispermatophores of Brachistosternus peruvianus Toledo-Piza and Brachistosternus pegnai Cekalovic are illustrated for the first time. A key to species of Brachistosternus and maps with the distribution of the subgenera and main groups of species are provided.